P38 Increasing access to simulation training using core medical training quality criteria. (3rd November 2019) - Armstrong, Miriam; Jones, Mike; Purva, Makani; Black, David
Abstract : Introduction: In 2015 the Joint Royal Colleges of Physicians Training Board (JRCPTB), acting on behalf of the three UK Royal Colleges of Physicians, launched a set of quality criteria designed to improve the educational experience of Core Medical Trainees (CMTs). Another major aim of the criteria was to ensure the CMT curriculum was systematically covered by the training programme, whilst helping to build trainee confidence in performing the role of General Internal Medicine Registrar, which requires being confident in practical procedures such as thoracentesis, abdominal paracentesis and in emergency presentations such as cardiac arrest. The implementation of the criteria would be monitored on a UK-wide basis using the General Medical Council's annual National Training Survey (GMC NTS). In addition, a UK-wide survey of CMT training programme directors was held in 2015 and 2016 to obtain their feedback (via an online survey with free-text responses) on local implementation. Methods: Following discussions at the joint JRCPTB/Health Education England (HEE) Expert Group on Simulation in CMT, amongst wider consultation, a simulation-specific 'quality criterion' was included and reflected in the GMC NTS from 2015 onwards: Skills laboratory and/or simulation training for all mandatory procedural skills to be provided at least once a year to supplement clinical training. Summary of results: There was a sequential increase in trainees' reported attendance at simulation training events with time (63%, 2015; 73%, 2016; 82%, 2017; 86%, 2018). Trainers consistently reported attendance at 90% and stated this training should be mandatory. Discussion, conclusions and recommendations: The findings demonstrate that centrally co-ordinated efforts to improve the provision of, and attendance at, curriculum-relevant simulation training can be effective, despite not being mandated in the curriculum and with no additional resources available for implementation. It is believed that the improvements reported by trainees were achieved through the co-ordinated efforts of the central promotion and drive for change arising from the three UK Colleges of Physicians together with a network of key stakeholders operating at a local level, including Heads of UK postgraduate schools of medicine, CMT training programme directors, supervisors, College tutors and their equivalents plus the support of the GMC to include relevant questions in their annual training survey. References: Joint Royal Colleges of Physicians Training Board. Quality criteria for core medical training. 2015. https://www.jrcptb.org.uk/cmtquality [Accessed 3 June 2019]. General Medical Council. National training surveys . https://www.gmc-uk.org/education/how-we-quality-assure/national-training-surveys [Accessed 3 June 2019].